Effects of Antitumor Necrosis Factor Therapy on Osteoprotegerin, Neopterin, and sRANKL Concentrations in Patients with Rheumatoid Arthritis. (21st October 2015) - Kurz, Katharina; Herold, Manfred; Russe, Elisabeth; Klotz, Werner; Weiss, Guenter; Fuchs, Dietmar
Abstract : Background . Rheumatoid arthritis is a systemic autoimmune disease characterized by joint erosions, progressive focal bone loss, and chronic inflammation. Methods . 20 female patients with moderate-to-severe rheumatoid arthritis were treated with anti-TNF-antibody adalimumab in addition to concomitant antirheumatic therapies. Patients were assessed for overall disease activity using the DAS28 score, and neopterin, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) concentrations as well as osteoprotegerin (OPG) and soluble receptor activator of NF- κ B ligand (sRANKL) concentrations were determined before therapy and at week 12. Neopterin as well as OPG and sRANKL were determined by commercial ELISAs. Results . Before anti-TNF therapy patients presented with high disease activity and elevated concentrations of circulating inflammatory markers. OPG concentrations correlated with neopterin (r s = 0.494, p = 0 . 027 ), but not with DAS28. OPG concentrations and disease activity scores declined during anti-TNF-treatment (bothp < 0 . 02 ). Patients who achieved remission (n = 7 ) or showed a good response according to EULAR criteria (n = 13 ) presented with initially higher baseline OPG levels, which subsequently decreased significantly during treatment (p = 0 . 018 for remission, p = 0 . 011 for good response). Conclusions . Adalimumab therapy was effective in modifying disease activity and reducing proinflammatory and bone remodelling cascades.